The Dynamics Encounter between Christianity and Toraja Culture in the Region of Buakayu-Mappa’ Tana Toraja - Tangirerung, Johana Ruadjanna; Bungaran, Stepanus Ammai; Timbang, Yekhonya F. T.; Rante, Yakob Sampe (Institut Agama Kristen Negeri Toraja, 2024)
The encounter between Christianity and Toraja culture has shaped the identity of Toraja Christian communities. However, Toraya Ma’kombongan's formulation revealed the fact that the hybrid identity resulting from this encounter has contributed to crises in various aspects. It appears that there is a void in this encounter filled with values such as materialism and hedonism. Therefore, this research aims to reexamine the mutual influence between Toraja culture and Christianity by selecting Mappa'-Buakayu as the research locus. This area was chosen for two reasons. First, Mappa'-Buakayu is known to be very open to Christianity. Second, the region is experiencing a cultural resurgence. This research employs qualitative research methods through fieldwork and literature review. Specifically, Robert J. Schreiter's map of local theology will be used to analyze the mutual influence between Christian theology and local theology that has shaped and influenced the lives of Toraja Christians in the Mappa'-Buakayu region. The results of the research indicate that the resurgence of interest in Toraja culture is triggered by several factors, namely tourism agendas, modernization, and an increasingly pluralistic society. These factors have a significant impact on redefining the identity of Toraja Christians in the Buakayu-Mappa' region while shaping the local face of the Toraja Church's theology.